José Antonio Corrales. Letters from America. - Martín Domínguez, Nicolás (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
For the Spanish Pavilion competition at the 1965 New York World’s Fair, Corrales and Molezún, surprisingly presented themselves. They would show, in this way, the individual confidence in their architectures, together with their personal courage that, after the shared success of Brussels, could be repeated here. Going alone, perhaps involved greater risk. Between 1962 and 1968, Corrales was presented alone to three more competitions as an advance or corollary of the American project section. I would also build a house today missing. From diverse programs, surfaces and locations, the transfer of ideas between them all becomes evident. The operations are repeated: on seemingly bland or complicated places, Corrales will invent new Places. The oblique section deposited in the place is the tool chosen by him. Its gradual improvement is revealed in its search to achieve its objectives. The section of the New York Pavilion is already clear, as a turning point. Fleeting as the Exhibition itself invites us to observe it with attention. Clear reference that allows us to appreciate what happened in his solo work in the previous and subsequent years. My weekly visits to his studio during 2010, allowed me to discover many projects, drawings and poems. Some of them unpublished see the light here for the first time. They are nothing other than the manifest essence of José Antonio Corrales himself.